1982
DOI: 10.1002/j.1460-2075.1982.tb01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer into mouse lyoma cells by electroporation in high electric fields.

Abstract: Electric impulses (8 kV/cm, 5 microseconds) were found to increase greatly the uptake of DNA into cells. When linear or circular plasmid DNA containing the herpes simplex thymidine kinase (TK) gene is added to a suspension of mouse L cells deficient in the TK gene and the cells are then exposed to electric fields, stable transformants are formed that survive in the HAT selection medium. At 20 degrees C after the application of three successive electric impulses followed by 10 min to allow DNA entry there resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
1,138
6
22

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,265 publications
(1,197 citation statements)
references
References 26 publications
9
1,138
6
22
Order By: Relevance
“…5,9,24,25 Although higher strength pulses (eg 500-3000 V/cm), with durations in the microsecond range, have been demonstrated to be useful in transfecting cells in vitro, [26][27][28] Lucas et al 29 demonstrated that low voltage, millisecond duration pulses resulted in a higher gene expression in vivo than high voltage, microsecond duration pulses. A reduction in pulse duration from a millisecond to a microsecond range may cause DNA electrophoresis to be ineffective, as found in our in vitro experiments using 2% agarose gels (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…5,9,24,25 Although higher strength pulses (eg 500-3000 V/cm), with durations in the microsecond range, have been demonstrated to be useful in transfecting cells in vitro, [26][27][28] Lucas et al 29 demonstrated that low voltage, millisecond duration pulses resulted in a higher gene expression in vivo than high voltage, microsecond duration pulses. A reduction in pulse duration from a millisecond to a microsecond range may cause DNA electrophoresis to be ineffective, as found in our in vitro experiments using 2% agarose gels (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In electroporation, an electrical pulse is applied to the cells, which induces transient permeability of the cell plasma membranes and results in the internalization of nucleic acids (Neumann et al 1982). As an optimized method of electroporation, nucleofection encompasses not only electrical pulse, but also cell typespecific solutions, resulting in superior transfection efficiency and cell viability, especially for difficult-totransfect cells (Maasho et al 2004;Bertram et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is now recognized as one of the most promising alternatives to viral vectors for transfection of different tissues in vivo for therapeutic purposes. [3][4][5] Gene therapy using electropulsation as a gene delivery method has already entered clinical trials for the treatment of different tumor types in cancer patients and for vaccination.…”
Section: Introductionmentioning
confidence: 99%